PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO ANIMASI UNTUK MENINGKAT PEMAHAMAN BELAJAR BAHASA INDONESIA KELAS III SD N 96 PALEMBANG - Yusni Arni; Nurhayati Nurhayati; Ailsa Intan Medika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT The development of animated video-based teaching materials to improve understanding of Indonesian language learning for class III, aims to determine the development of valid, practical and effective understanding of Indonesian language learning. The type of research used by researchers in developing this animated video-based teaching material is research and development, development refers to the ADDIE model consisting of Analysis design, development, implementation, and evaluation. The research subjects were students in classes IIIA and IIIB at State Elementary School 96 Palembang with a total of 36 students. The data collection techniques used in the research were questionnaires and documentation, based on the results of research by expert validators from three fields, namely media, materials and language, where the validators in In this development, there are 2 validators covering these three fields, so that the percentage of validators from the two experts of 3.80 is categorized as "valid". Then the practicality test of the teacher's response obtained a percentage result of 87.49%, categorized as "very practical", then the one to one trial obtained a percentage value of 87.49%, categorized as very practical, then the small group trial obtained a percentage value of 79.27 %. And the final test of the potential effect test obtained a percentage value of 90.00% which was categorized as very effective. Keywords: Development of teaching materials, animated videos, Indonesian